Comparative analysis of shot and laser shock peening in AA7075 aluminium alloy - Mokolobate, Kenosi (My University, 2019)
Shot Peening (SP) is a widely used technique to improve the mechanical properties of metallic surfaces in the industry and is one of the most effective techniques of inducing residual compressive stresses into metal surfaces to enhance their fatigue performance. The SP processing is inexpensive. It has been used in different applications; however, the process has its limitations. The laser shock peening (LSP) process has been successfully used to introduce residual compressive stresses in metals. This process is an alternative surface processing technology to the SP. It has been used for medical implants, in nuclear power reactors, aircraft panel forming, and treatment of aircraft engine components. Whilst the SP and the LSP create residual stresses of similar magnitude, the LSP was found to induce residual stresses with greater depth into the metallic material. These residual stresses reached up to five times deeper and produced a uniform peening effect across the surface of the material compared to the SP making the LSP more appealing to the aviation industry. This research was limited to residual stress, surface roughness, microstructure, and microhardness measurements on the SP and LSP-treated AA7075-T651 conventional aeronautical aluminium alloy. The incremental hole drilling technique was mostly used to analyse compressive residual stresses in the treated material and complimentary measurements on the surface were performed using the X-Ray Diffraction method. It was found that the SP and the LSP processes produced compressive residual stresses (RS) in AA7075-T651. Compressive RS were found to be deeper in the LSP compared to those produced through SP. The surface roughness was higher in SP-treated samples compared to the LSP-treated samples. There were no appreciable changes to the microstructure of peened samples in both conditions. Both the SP and the LSP resulted in hardened regions within the surface layer of the AA7075-T651; with LSP generating higher microhardness in comparison to SP.
A research report proposal submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfillment of the requirements for the degree of Masters in Engineering March, 2019
Keywords: Aluminum alloys--Testing; Metallurgy--Laser use in; Laser peening